2014
DOI: 10.1186/1472-6882-14-491
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl acetate extract of Wedelia chinensis inhibits tert-butyl hydroperoxide-induced damage in PC12 cells and D-galactose-induced neuronal cell loss in mice

Abstract: BackgroundWedelia chinensis is traditionally used as a hepatoprotective herb in Taiwan. The aim of this study was to evaluate the neuroprotective potential of W. chinensis.MethodsAn ethyl acetate extract of W. chinensis (EAW) was prepared and analyzed by HPLC. The neuroprotective potential of EAW was assessed by tert-butylhydroperoxide (t-BHP)-induced damage in PC12 cells and D-galactose-induced damage in mouse cortex.ResultsEAW exhibited potent radical scavenging property and highly contained luteolin and wed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…ROS are predominantly produced in mitochondria. It has been reported that the mitochondria-dependent apoptotic pathway is involved in t -BHP-induced cytotoxicity, in which the Bcl-2 family proteins play a key role [ 24 ]. The anti-apoptotic Bcl-2 bind to the outer membrane of the mitochondria can stabilize the membrane permeability and prevent the release of cytochrome c [ 25 ], while the pro-apoptotic members like Bax are responsible for permeabilizing membrane under cellular stress [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…ROS are predominantly produced in mitochondria. It has been reported that the mitochondria-dependent apoptotic pathway is involved in t -BHP-induced cytotoxicity, in which the Bcl-2 family proteins play a key role [ 24 ]. The anti-apoptotic Bcl-2 bind to the outer membrane of the mitochondria can stabilize the membrane permeability and prevent the release of cytochrome c [ 25 ], while the pro-apoptotic members like Bax are responsible for permeabilizing membrane under cellular stress [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…We observed in the present study that treatment with 300 mM Dg for 48 h induced cellular senescence in SY5Y cells. Previously, it was reported that Dg treatment efficiently induced senescence not only in animal models, but also in in vitro cell models [ 12 33 34 ]. For example, Wang et al [ 35 ] and Rahimi et al [ 36 ] reported that 200–400 mM Dg could cause senescence in RA-induced differentiated SY5Y cells as a result of increased oxidative stress and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…As a frequent event in nervous system, it is therefore associated with a wide range of neurological diseases (1,2). OS is an important therapeutic target, and the supplement of exogenous antioxidants has been validated to be an effective approach to prevent and manage neurological diseases clinically (13)(14)(15)(16). In the present study, neuronal SH-SY5Y cells underwent OS following exposure to H 2 O 2 , as indicated by TAC and MDA assays, and post-treatment with α-Naphthoflavone and/or β-Naphthoflavone effectively alleviated H 2 O 2 -induced OS.…”
Section: Discussionmentioning
confidence: 99%